The Old Gays guide to the good life : lessons learned about love and death, sex and sin, and saving the best for last (HarperWave, an imprint of HarperCollinsPublishers, 2023)
America's most beloved foursome--the TikTok sensation @theoldgays--share humorous, heartbreaking, shocking and profound tales from their generation, revealing who they are beyond TikTok and offering collective wisdom on a rainbow of topics as they prove age is just a number and getting older can be fabulously fun.